PERANAN SEKTOR BASIS TERHADAP PENYERAPAN TENAGA KERJA DI KABUPATEN GRESIK - SELIFIA FIFI INDRIATY (Jurnal Pendidikan Ekonomi (JUPE), 2013)
This study aimed to determine the role of the base sector to the labour absorption in Gresik regency. This research is quantitative descriptive study using the LQ (Location Quotient) and methods of analysis of labor absorption. Results of this study explain that Gresik has two base sectors, namely Manufacturing sector, and Mining and Quarrying; Electricity, Gas, and Water supply. Manufactoring sector as the main base sector have a high employment elasticity negative amounted to -0.076 which means that if there is an increase of 1 percent GDP will decline in employment by 0,076 percent. While the Mining and Quarrying sector, electricity, gas and water supply have high levels of employment elasticity positive of 2.31 which means that if there is an increase of 1 percent GDP, there will be increase in employment of 2.31 percent. Keyword: Base Sector, Employment